2017
DOI: 10.1111/cup.13005
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous syncytial myoepithelioma: A recently described neoplasm which may mimic nevoid melanoma and epithelioid sarcoma

Abstract: Cutaneous syncytial myoepithelioma is a recently described rare tumor of the dermis. It is derived and composed purely of myoepithelial cells and shows a characteristic syncytial growth pattern of neoplastic cells with little intervening stroma and no recognizable ductal structures. It represents a diagnostic challenge to dermatopathologists given its rarity and unusual immunophenotype. Molecular testing for rearrangement of the EWSR1 gene plays a significant role in confirming the diagnosis in most cases. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 20 publications
(38 reference statements)
1
30
0
Order By: Relevance
“…These tumors are negative for CK by immunohistochemistry unlike CM and have distinctive molecular characteristics [8]. These tumors are benign such as CM and rarely recur when incompletely resected [7,8] In the current study, we also reported a CSM case with dermis-located and well-cirumscribed tumor displays a showed pseudoepitheliomatous hyperplasia (Figure 1 Immunohistochemically, cellular neurothekoma exhibits no positivity for EMA or S100 [11]. [15].…”
Section: Introductionsupporting
confidence: 50%
“…These tumors are negative for CK by immunohistochemistry unlike CM and have distinctive molecular characteristics [8]. These tumors are benign such as CM and rarely recur when incompletely resected [7,8] In the current study, we also reported a CSM case with dermis-located and well-cirumscribed tumor displays a showed pseudoepitheliomatous hyperplasia (Figure 1 Immunohistochemically, cellular neurothekoma exhibits no positivity for EMA or S100 [11]. [15].…”
Section: Introductionsupporting
confidence: 50%
“…Of interest, reports describing and illustrating this type of ME neoplasm in the skin were published in the literature of dermatopathology long before the coining of the term “cutaneous syncytial myoepithelioma.” Histopathologically, the lesion forms an unencapsulated dermal nodule, similar to that seen in other cutaneous myoepitheliomas, and like those tumors it exhibits a range of cytological appearances including spindled, ovoid, and/or epithelioid cells with pale eosinophilic cytoplasm and monomorphous nuclei displaying fine chromatin and small nucleoli . The syncytial arrangement of the cells is characteristic, with little or no intervening stroma and absence of ductal or glandular structures . Mitotic activity is infrequent, and when present does not alter the diagnosis or prognosis .…”
Section: Discussionmentioning
confidence: 77%
“…The true incidence of CSM, a recently recognized variant of cutaneous ME tumors, is unknown . To date, it has occurred predominantly in men, across a broad age range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The syncytial variant of cutaneous myoepithelioma is a reproducible cutaneous subtype with a dome-shaped silhouette and sheets or syncytia of epithelioid, plasmacytoid, and/or spindled cells with ovoid monomorphous nuclei. 7,8,11,12 The immunophenotype is often variable, sometimes overtly inconsistent with conventional myoepithelioma, which produces pitfalls in diagnosis. Immunopositivity with S100, EMA, and SMA are most frequent.…”
Section: Discussionmentioning
confidence: 99%